2017
DOI: 10.1063/1.5005174
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of cylindrical imploding underwater shockwaves at very small radii

Abstract: We compare the convergent shockwaves generated from underwater, cylindrical arrays of copper wire exploded by multiple kilo-ampere current pulses on nanosecond and microsecond scales. In both cases, the pulsed power devices used for the experiments had the same stored energy ( 500 J) and the wire mass was adjusted to optimize energy transfer to the shockwave. Laser backlit framing images of the shock front were achieved down to the radius of 30 l m. It was found that even in the case of initial azimuthal non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Researchers from Israel Institute of Technology verified the metal equation of state (EOS) and conductivity model based on nanosecond and microsecond time-scale UEWE [41][42][43]. Cylindrical and spherical wire arrays were used to generate convergent underwater shock waves (SWs) with pressure as high as 6.6 TPa and water compression ratio ∼9 [44]; a large amount of research on SW converging process and water state at extreme pressure [45][46][47][48][49][50][51][52] has been carried out in Israel Institute of Technology, Imperial College London, Tsinghua University, etc. Taking advantage of the high energy deposition, UEWE is used to synthesize metal nanoparticles with smaller diameter and narrower size distribution than the gas medium EWE [53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from Israel Institute of Technology verified the metal equation of state (EOS) and conductivity model based on nanosecond and microsecond time-scale UEWE [41][42][43]. Cylindrical and spherical wire arrays were used to generate convergent underwater shock waves (SWs) with pressure as high as 6.6 TPa and water compression ratio ∼9 [44]; a large amount of research on SW converging process and water state at extreme pressure [45][46][47][48][49][50][51][52] has been carried out in Israel Institute of Technology, Imperial College London, Tsinghua University, etc. Taking advantage of the high energy deposition, UEWE is used to synthesize metal nanoparticles with smaller diameter and narrower size distribution than the gas medium EWE [53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because of the rapid volume expansion of the wire (or metallic plasma), strong shock wave (SW) is generated during UEWE, which have many potential applications including extracorporeal lithotripsy, reservoir stimulation, electrohydraulic forming, non-thermal food processing and so on [8][9][10]. Underwater electrical explosion of wire arrays has been carried out to generate extremely high pressure (~10 11 Pa) in the center of the array, which can be used to study the extreme state of matters [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Yanuka et al observed the uniformity of cylindrical converging shock waves at a very small radius using laser backlit framing images. It was found that the shock front was rather azimuthally non-uniform down to the radius of ∼190 µm, but they believed that self-repairing can be completed in the final convergence stages [8]. The latest experimental results reported by Rososhek et al have shown that the shock wave front kept its azimuthal uniformity as far as the radius of 30 µm [9].…”
Section: Introductionmentioning
confidence: 99%